Consumer ethics: An empirical investigation of the ethical beliefs of Austrian consumers - Rawwas, Mohammed Y. A. (Journal of business ethics, 1996)
Business and Marketing ethics have come to the forefront in recent years. While consumers have been surveyed regarding their perceptions of ethical business and marketing practices, research has been minimal with regard to their ethical beliefs and ideologies. In addition, no study has examined the ethical beliefs of Austrian consumers even though Austria maintains a unique status of political neutrality, nonalignment, stability, economic prosperity and geographical proximity to the East- and West-European countries. This research investigates the relationship between Machiavellianism, ethical ideology and ethical beliefs of Austrian consumers. The results indicate that Austrian consumers are mostly “situationists” who, while rejecting moral rules, judge the ethics of a behavior by the consequences and outcomes of the situation.